A Fenton-like system of biochar loading Fe–Al layered double hydroxides (FeAl-LDH@BC) / H2O2 for phenol removal. (March 2021) - Xiaoliang Fan,; Cao, Qingqing; Meng, Fanyue; Song, Bing; Bai, Zhongqiang; Zhao, Yan; Chen, Dandan; Zhou, Yan; Song, Min
Abstract: FeAl-layered double hydroxide (FeAl-LDH) supported by char was synthesized using the hydrothermal method in order to activate hydrogen peroxide (H2 O2 ) to degrade phenol. The effects of char type, char synthesis amount, and several important parameters on the degradation were investigated. In addition, the physicochemical properties of FeAl-LDH@BC were revealed by instruments including the transmission electron microscope (TEM), X–ray diffraction (XRD), and Fourier–transform infrared (FT–IR). The results showed that the degradation efficiency of phenol (80 mg/L) by FeAl-LDH@BC0.25 was 85.28% at a pH of 3 and H2 O2 concentration of 400 mg/L, and exhibited good reusability with a small amount of iron leaching. Electron paramagnetic resonance (EPR) and radical quenching results indicated that ·OH radicals were the main participant during the degradation process, and XRD and FTIR spectra showed that FeAl-LDH was dissolved and rebuilt during the degradation process, and a small amount of iron was leached out resulting in the homogeneous catalysis. Hence, both homogeneous and heterogeneous processes occurred in the phenol oxidation process. Further soil remediation experiments showed that FeAl-LDH@BC0.25 could also effectively degrade phenol in soil, although the efficiency was lower than that in solution. Graphical abstract: Image 1 Highlights: Fe-Al layered double hydroxides loaded on rice husk biochar (FeAl-LDH@BC) was successfully synthesized. FeAl-LDH@BC/H2 O2 system could effectively remove phenol in solution and soil, and exhibited repeatability in solution. The hydroxyl radicals (·OH) played an important role in the FeAl-LDH@BC/H2 O2 system.